3+ln(27x)=18-2ln(x)

Simple and best practice solution for 3+ln(27x)=18-2ln(x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3+ln(27x)=18-2ln(x) equation:


Simplifying
3 + ln(27x) = 18 + -2ln(x)

Remove parenthesis around (27x)
3 + ln * 27x = 18 + -2ln(x)

Reorder the terms for easier multiplication:
3 + 27ln * x = 18 + -2ln(x)

Multiply ln * x
3 + 27lnx = 18 + -2ln(x)

Multiply ln * x
3 + 27lnx = 18 + -2lnx

Solving
3 + 27lnx = 18 + -2lnx

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '2lnx' to each side of the equation.
3 + 27lnx + 2lnx = 18 + -2lnx + 2lnx

Combine like terms: 27lnx + 2lnx = 29lnx
3 + 29lnx = 18 + -2lnx + 2lnx

Combine like terms: -2lnx + 2lnx = 0
3 + 29lnx = 18 + 0
3 + 29lnx = 18

Add '-3' to each side of the equation.
3 + -3 + 29lnx = 18 + -3

Combine like terms: 3 + -3 = 0
0 + 29lnx = 18 + -3
29lnx = 18 + -3

Combine like terms: 18 + -3 = 15
29lnx = 15

Divide each side by '29nx'.
l = 0.5172413793n-1x-1

Simplifying
l = 0.5172413793n-1x-1

See similar equations:

| 2(y+3y)=84 | | 7(7x+6y-9)+4(8x-4)= | | -9x-10+3x-4= | | 3*x+4=1 | | 21=60-12x | | a+(10-3)=30+10a | | 5-8*x=11 | | -56=-c-(-8) | | 4x+5=6.5 | | 3n^2+9n-12=0 | | 2(x+2)-5(2x+7)= | | 7x+2=-103 | | 2x+10-3=-2x+1 | | 10-2*x=4 | | -.75+j=-3.5 | | 4x+126=11x | | 19-2*x=4 | | 96=-24c | | -6a-5b-4= | | -3.75+j=-3.5 | | 96=-24 | | 4-3*x=34 | | 2x+7y+8= | | (v-3)(2v+1)= | | 6a-5b-4= | | 2-6*x=5 | | z^3-3z^2+(1+3i)z-6i+a=0 | | 2a^2-ab-15b^2=0 | | .5*x+1=11 | | c=15+40 | | 4x+10=x+37 | | -4+2t=1 |

Equations solver categories